A recruitment model for beech–oak pure and mixed stands in Belgium. (26th November 2019) - Manso, Rubén; Ligot, Gauthier; Fortin, Mathieu
Abstract: We present a recruitment model for pure and mixed beech and oak stands in Belgium, the first empirical model for this forest type in this geographical area. Data from the Wallonia National Forest Inventory were used to fit the model. We adopted a zero-inflated formulation where model parameters governing species' behaviour were simultaneously fitted. Plot random effects specific to each species were included, the simultaneous fit allowing them to correlate. Model predictions proved accurate and corresponded to current ecological knowledge about the regeneration dynamics of this kind of mixture. While our model could potentially be used to complement the existing beech and oak growth models for this region of Europe, our results also show that beech recruits tend to dominate regardless of the oak share in the overstorey composition and the stand stocking. This confirms that the beech–oak mixture may not be stable under the conditions of the study area and current management aimed at promoting continuous forest cover.